Primary Versus Salvage Reverse Total Shoulder Arthroplasty for Displaced Proximal Humerus Fractures in the Elderly: A Systematic Review and Meta-analysis. (September 2020) - Nelson, Patrick A; Kwan, Changyow C; Tjong, Vehniah K; Terry, Michael A; Sheth, Ujash
Background: There is currently no established consensus on best treatment for complex proximal humerus fractures (PHFs) in the elderly. Reverse total shoulder arthroplasty (RTSA) is a viable option in this population but many times is used as a salvage procedure. Methods: A systematic review of studies comparing RTSA as a primary treatment for PHF versus as a salvage procedure following failed open reduction internal fixation (ORIF), humeral intramedullary nailing, hemiarthroplasty (HA) or non-operative treatment was conducted using PRISMA guidelines. Pooled outcomes and sub-group analyses assessing range of motion, patient reported outcomes and complications were examined using RevMan. Results: Five articles were included in final analysis with 104 patients in the primary RTSA group and 147 in the salvage RTSA group compromising 251 total patients. Primary RTSA had a statistically significant advantage in range of motion (forward flexion and external rotation), patient reported outcomes, and complications compared to salvage RTSA. Conclusions: Based on the best available evidence, primary RTSA may result in slightly better patient reported outcomes, range of motion and a lower rate of complication when compared to salvage RTSA. Further high-quality prospective studies are needed to confirm the findings of the current review.